Increased the Role of Defense Human Resources in Facing of the Threats - Pertiwi, Ayu; Novky Asmoro; Prakoso, Lukman Yudho (PT FORMOSA CENDEKIA GLOBAL, 2024)
National defense is all efforts to defend state sovereignty, territorial integrity, and the safety of the entire nation from threats and disturbances to the integrity of the nation and state. The problems of national defense, which are increasingly varied in the development of the threat spectrum, certainly require reliable human resources for implementing or making national defense policies. Indonesia with a large population certainly has great potential in the procurement of defense resources. However, if the quality cannot keep up with current threat dynamics and technology then the number is meaningless. The purpose of this research is to find out how to increase the role of Indonesian defense human resources to deal with threats that occur to realize national security. The research method used in this study is a qualitative descriptive analysis method with data collection techniques through literature and library studies. The results of this study are that the government’s role is very important in increasing the superiority of defense human resources. Such as providing training, education, providing motivation, and synergizing with institutions and parties related to the defense industry to improve HR capabilities in dealing with technological advances